2015
DOI: 10.1136/bmj.h1314
|View full text |Cite
|
Sign up to set email alerts
|

The role of pathogen genomics in assessing disease transmission

Abstract: Whole genome sequencing (WGS) of pathogens enables the sources and patterns of transmission to be identified during specific disease outbreaks and promises to transform epidemiological research on communicable diseases. This review discusses new insights into disease spread and transmission that have come from the use of WGS, particularly when combined with genomic scale phylogenetic analyses. These include elucidation of the mechanisms of cross species transmission, the potential modes of pathogen transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 134 publications
2
84
0
Order By: Relevance
“…The dramatic increase in the amount of genomic data being published will increase the likelihood of designing and applying an alternative genotyping method which better encompasses the likely genetic divergence of Cryptosporidium spp., in order to complement or improve upon the current genotyping methods (2). Ultimately, such a panel or library would facilitate the implementation and transfer of Cryptosporidium genotyping to NGS platforms, as has been demonstrated for other pathogens (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dramatic increase in the amount of genomic data being published will increase the likelihood of designing and applying an alternative genotyping method which better encompasses the likely genetic divergence of Cryptosporidium spp., in order to complement or improve upon the current genotyping methods (2). Ultimately, such a panel or library would facilitate the implementation and transfer of Cryptosporidium genotyping to NGS platforms, as has been demonstrated for other pathogens (14).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are limitations to the genotyping resolution of gp60 that have led to multiple studies looking into the potential use of multilocus sequence typing (MLST) in order to infer the population structures of Cryptosporidium (10)(11)(12) without generating any consensus list of genetic markers. The advent of next-generation sequencing (NGS) has led to an immense interest in public health pathogen genome sequencing (13,14) as an alternative to MLST. Despite the generation of several complete genomes, including those of C. parvum (15) and C. hominis (16,17), the lack of long-term culturing capabilities and the general dearth of sufficient clinical material have made it difficult to extract enough target-specific DNA for sequencing Cryptosporidium genomes on a routine basis.…”
mentioning
confidence: 99%
“…These loci provide limited resolution at the spatio-temporal scale necessary for describing the relatively recent B. microti invasion in northeastern U.S. because of their low genetic diversity. Whole genome level analyses provide a powerful tool to explain origin, patterns and dynamics of spread, as they contain more genetic diversity than individual genes [15]. The first complete genome sequence of a B. microti isolate was reported in 2012 [16] and showed that the parasite is significantly distant from other apicomplexan taxa, including Babesia bovis and Theileria species.…”
Section: Introductionmentioning
confidence: 99%
“…Since those first studies, the use of genomics to understand TB transmission has dramatically increased, with 27 papers and over 5000 Mtb genomes to date (Table ). Genomic epidemiology is also being applied in the larger clinical microbiology space, with studies of everything from food‐ and water‐borne pathogens to hospital‐acquired infections, as highlighted in several recent reviews . Pathogen genomics has become an integral part of many national public health agencies’ routine practice, with groups, such as Public Health England (PHE), the U.S. Centers for Disease Control and Prevention (CDC), and the Public Health Agency of Canada (PHAC), all engaged in genomic surveillance.…”
Section: Leveraging Genomics For Epidemiologymentioning
confidence: 99%